2015
DOI: 10.1002/2015jd023322
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of global aerosol type as retrieved by MISR

Abstract: In addition to aerosol optical depth (AOD), aerosol type is required globally for climate forcing calculations, constraining aerosol transport models and other applications. However, validating satellite aerosol-type retrievals is more challenging than testing AOD results, because aerosol type is a more complex quantity, and ground truth data are far less numerous and generally not as robust. We evaluate the Multiangle Imaging Spectroradiometer (MISR) Version 22 aerosol-type retrievals by assessing product sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
229
0
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 215 publications
(237 citation statements)
references
References 76 publications
7
229
0
1
Order By: Relevance
“…The MISR particle types and mixtures are designed to represent several compositional categories typically found in the atmosphere, such as sea spray, sulfate, nitrate, mineral dust, carbonaceous, and urban soot aerosols. Recently, Kahn and Gaitley (2015) provided a thorough verification of MISR's aerosol type retrieval capabilities and Lee et al (2016) demonstrated that the MISR aerosol particle climatologies regionally showed good agreement with the results of chemical transport models. The current 74 mixture set, however, is not complete and has some documented deficiencies Kalashnikova et al, 2013;Limbacher and Kahn, 2014).…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…The MISR particle types and mixtures are designed to represent several compositional categories typically found in the atmosphere, such as sea spray, sulfate, nitrate, mineral dust, carbonaceous, and urban soot aerosols. Recently, Kahn and Gaitley (2015) provided a thorough verification of MISR's aerosol type retrieval capabilities and Lee et al (2016) demonstrated that the MISR aerosol particle climatologies regionally showed good agreement with the results of chemical transport models. The current 74 mixture set, however, is not complete and has some documented deficiencies Kalashnikova et al, 2013;Limbacher and Kahn, 2014).…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
“…The V22 operational algorithm defines 74 aerosol mixtures, each of which consists of up to three unique particle types having prescribed optical and microphysical properties Kahn and Gaitley, 2015). The 74 mixtures consist of combinations of eight primary particle types.…”
Section: Previous Misr V2dark Water Algorithmmentioning
confidence: 99%
“…The best-fitting mixture out of the 74 candidate mixtures is reported as the "RegLowestResidMixture", but the AOD and information about which mixtures were considered passing are retained in the fields "OptDepthPerMixture" and "AerRetrSuccFlagPerMixture", respectively, for further evaluation. Validation of the Level 2 Version 22 product against ground-based observations from the Aerosol Robotic Network (AERONET) (Holben et al, 1998), including assessments of particle type retrievals, can be found in Kahn et al (2010) and Kahn and Gaitley (2015). The mixture type information in the MISR Version 22 aerosol product has been exploited by Li et al (2013) and Li et al (2015), for example, who used CCM in-formation to select from the complete set of passing mixtures to improve agreement with AERONET in the continental United States.…”
Section: Introductionmentioning
confidence: 99%
“…However, neither one of these instruments were specifically designed to retrieve aerosol properties. The more recent dedicated aerosol sounders, such as ATSR (The Along Track Scanning Radiometer 2, LlewellynJones and Remedios, 2012), MODIS (Moderate Resolution Imaging Spectroradiometer, Levy et al, 2010), VIISR (Visible Infrared Imaging Radiometer Suite, Jackson et al, 2013) and MISR (Multi-angle Imaging SpectroRadiometer, Kahn and Gaitley, 2015) offer data from 1995, 2000 and 2002 onwards respectively. It is therefore apparent that neither sun photometer nor satellite records of AOD are available for all the decades where industrialization has had a significant effect on the aerosol load.…”
Section: Introductionmentioning
confidence: 99%